Signs of life. An introduction - Fermín A. Rodríguez (Universidad Nacional de Mar del Plata, 2021)
Precarious life emerges in the Latin American novel as an index of deterritorialization processes that, imperceptibly, have been altering since the last decades of the 20th century the linguistic, perceptual and practical coordinates within which we think and imagine Latin America, its power structures, the order of its discourses and the grid of its things and bodies. Signs of Life is a reading of the 90s and early 2000s that wants to give an account of a series of writings that find their politics in precarious life. Precariousness is the fundamental impulse of a series of texts that experiment with the vulnerability of the living, relating precariousness as an instrument of government with changes in language, vision and perception generated by the crisis. Suspicious of formal perfection, fictions of life turned the precariousness of existence into a field of experimentation and disputes over time and territory. Texts by, among others, Fogwill, Diamela Eltit, Sergio Chejfec, César Aira, Matilde Sánchez and Gabriela Cabezón Cámara, survive the catastrophe to tell what happened and emit, beyond the end of history, the signs of life of a literature to come.